THE NECESSITY OF A HIERARCHY OF THE SYSTEM OF NORMATIVE ACTS AND PRINCIPLE OF THE SUPREMACY OF THE CONSTITUTION - GRIGORE-RĂDULESCU, Maria-Irina (International Journal of Legal and Social Order, 2022)
In the approach and substantiating the hierarchy of the system of normative acts and the principle of the supremacy of the Constitution, we started from the idea that the relationship of legal norms, which gives substance to any system of law, must be characterized by unity, functionality and, last but not least, by hierarchy. My study is mainly about the Romanian law system, but it also includes some generality observations, applicable to all national law systems.